2020
DOI: 10.1101/2020.12.21.423658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Independent human mesenchymal stromal cell-derived extracellular vesicle preparations differentially affect symptoms in an advanced murine Graft-versus-Host-Disease model

Abstract: Extracellular vesicles (EVs) harvested from cell culture supernatants of human mesenchymal stromal cells (MSCs) suppress acute inflammation in preclinical models of various diseases. Furthermore, they promote regeneration of damaged tissues. Following successful clinical treatment of a steroid-refractory Graft-versus-Host-Disease (GvHD) patient with EVs prepared from conditioned media of human bone marrow (BM)-derived MSCs, we aim to improve MSC-EV production and quality control towards clinical application. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 42 publications
(69 reference statements)
4
19
0
Order By: Relevance
“…Indeed, despite treatment with similar particle numbers of EVs isolated from donor 16.3 MSCs compared to 41.5, the investigated features were not reduced and were comparable to NPC1 −/− mice treated with vehicle or platelet derived EVs. These results are in agreement with the in vitro immunomodulatory capacity of both MSC-EV fractions [ 32 , 33 ]. Consequently, functional testing of any MSC-EV preparation is necessary prior to clinical application.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Indeed, despite treatment with similar particle numbers of EVs isolated from donor 16.3 MSCs compared to 41.5, the investigated features were not reduced and were comparable to NPC1 −/− mice treated with vehicle or platelet derived EVs. These results are in agreement with the in vitro immunomodulatory capacity of both MSC-EV fractions [ 32 , 33 ]. Consequently, functional testing of any MSC-EV preparation is necessary prior to clinical application.…”
Section: Discussionsupporting
confidence: 89%
“…Although both obtained MSC-EV preparations (MSC16.3-EV and MSC41.5-EV) revealed comparable EV characteristics, we previously reported that they exert different activities in an ischemic stroke as well as an optimized murine graft-versus.-host disease (GvHD) model and differed in their ability to modulate allogenic immune responses in vitro. Indeed, while the MSC41.5-EV preparation showed immunomodulatory activities in both animal models and in vitro, MSC16.3-EV failed to show therapeutic efficacy [ 32 , 33 ]. To compare their impact on typical systemic and neurologic features of the early-onset NPC1 pathology, aliquots of both MSC-EV preparations and of an EV preparation obtained from fresh, human platelet lysate supplemented MSC cultivation media (PL EV) were repetitively administered to NPC1 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following 5 days in culture, approximately a quarter of all CD4 + T cells express the interleukin-2 receptor (CD25) and the intercellular adhesion molecule-1 (CD54), indicating T cell activation (Figure 4). As previously described, MSC-EV preparations with immunomodulatory capabilities effectively reduce the content of activated CD4 + T cells (Madel et al, 2020). Consistently, in the presence of the non-labelled MSC-EV preparations only 16% of the monitored CD4 + T cells were found to display the activation cell surface markers (Figure 4B).…”
Section: Exoria Staining Does Not Affect the Immunomodulatory Capacity Of The Msc-ev Preparationssupporting
confidence: 85%
“…The immunomodulatory potential of Exoria labelled and non-labelled MSC-EV preparations were compared in a multi-donor mixed lymphocyte reaction assay (MLR) exactly as described previously (Madel et al, 2020). Briefly, Ficoll prepared peripheral blood mononuclear cells (PBMC) of 12 healthy donors were mixed in equal proportions, aliquoted and stored in the vapour phase of liquid nitrogen until usage.…”
Section: Multi-donor Mixed Lymphocyte Reaction (Mdmlr)mentioning
confidence: 99%